Optimizing the use of temporal artery biopsy: a retrospective study - Etienne Villeneuve; Jean-Michel Lacroix; Simon Brisebois (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Giant cell arteritis is an inflammatory disease of the large- and medium-sized vessels. It is the most common primary vasculitis, with lifetime incidences of 0.5% and 1% in men and women, respectively. Its diagnosis is based upon clinical criteria, which may include temporal artery biopsy. Expected positivity rates of temporal artery biopsies and patient selection remain controversial topics in the literature. Methods A cross-sectional retrospective study of 127 patients referred for temporal artery biopsy with a diagnosis of suspected giant cell arteritis between January 2014 and December 2018 was performed. The primary outcome was the positivity rate. The relationships between positivity rates, symptoms, clinical suspicion, biopsy delay, biopsy length and corticosteroid treatment were also studied. Results A positivity rate of 23.7% (16.6–32.6%) was shown, along with a significant association between jaw claudication and specimen positivity (odds ratio 8.1, p < 0.05). Moreover, there were significant associations between a high initial clinical suspicion of disease and specimen positivity (p < 0.05), as well as a high initial clinical suspicion of disease and pursuit of corticosteroid treatment following biopsy results, regardless of positivity (p < 0.05). The duration of corticosteroid treatment prior to biopsy was not associated with a change in positivity rate. Conclusions The positivity rate of temporal artery biopsy was 23.7%. Treatment of patients with negative temporal artery biopsy was associated with maintenance of corticosteroid treatment when the initial clinical suspicion of arteritis was high. Therefore, temporal artery biopsy may not be necessary for patients with a high initial clinical suspicion of giant cell arteritis. Graphical Abstract